The walls have eyes : surviving migration in the age of artificial intelligence - Molnar, Petra (Lawyer) (The New Press, 2024)
"An expose of the inhumane and lucrative sharpening of borders around the globe through experimental surveillance technology"-- Provided by publisher.
"Foreword by E. Tendayi Achiume"--PDF image of copyright page.
Keywords: Border security -- Technological innovations.; Emigration and immigration -- Technological innovations.; Artificial intelligence -- Political aspects.; Diplomacy.; International relations.; Social sciences.; Electronic books.; Sécurité frontalière -- Innovations.; Émigration et immigration -- Innovations.; Intelligence artificielle -- Aspect politique.; Diplomatie.; Relations internationales.; Sciences sociales.; Livres numériques.; diplomacy.; international relations.; social sciences.; e-books.; Emigration & Immigration.; LAW.; International Relations.; POLITICAL SCIENCE.; Security (National & International); SOCIAL SCIENCE.; POLITICAL SCIENCE / Public Policy / Immigration